Total and Gleason grade 4/5 cancer volumes are major contributors of human kallikrein 2, whereas free prostate specific antigen is largely contributed by benign gland volume in serum from patients with prostate cancer or benign prostatic biopsies. - Haese, A; Graefen, M; Steuber, T; Becker, C; Noldus, J; Erbersdobler, A; Huland, E; Huland, H; Lilja, H (2003)
PURPOSE: We measured concentrations of human glandular kallikrein 2 (hK2), total prostate specific antigen (tPSA), free PSA (fPSA) and percent fPSA to evaluate their relationship to total prostate gland volume, benign prostatic hyperplasia (BPH) volume, total prostate cancer (PCa) volume (CaVol) and the volume of Gleason grades 4/5 cancer (CaVolGl4) in the serum of 256 patients with PCa undergoing radical retropubic prostatectomy and 185 with negative systematic sextant biopsies. MATERIALS AND METHODS: Free and total PSA was measured using the Delfia Prostatus (Perkin-Elmer, Turku, Finland) total/free PSA assay and hK2 was measured using a research immunofluorometric assay. Transrectal ultrasound was used to determine total prostate and BPH volume. Total CaVol and CaVolGl4/5 were calculated using a volumetric program in specimens from 158 men with pT2a/b and 98 with pT3a or greater PCa. The Pearson correlation was performed after logarithmic conversion of PSA and hK2 levels. Benign gland, and pT2a/b and pT3a or greater PCa cases were subdivided into small vs large prostate gland volumes (42 cc or less vs greater than 42 cc). RESULTS: Total prostate and BPH volumes correlated closely with free PSA (r = 0.64 to 0.65, p <0.0001) in 143 patients with negative biopsy and a prostate of greater than 42 cc. Correlations of hK2 and tPSA with total prostate and BPH volumes were weaker (r = 0.35 to 0.36 and 0.45 to 0.46, respectively). In pT2a/b and pT3a or greater PCa cases hK2 most closely correlated with CaVol (range 0.31 to 0.62, p = 0.0072 and <0.0001) and with CaVolGl4/5 (range 0.26 to 0.56, p = 0.021 and <0.0001, respectively). The tPSA level correlated significantly with CaVol and CaVolGl4/5 except in glands 42 cc or greater harboring pT2a/b PCa (p = 0.08). Free PSA correlated significantly with CaVolGl4/5 only in pT3a or greater PCa (p <0.05), and with CaVol in pT3a or greater PCa and in small prostates harboring pT2a/b PCa. CONCLUSIONS: Large benign prostate gland volume affects fPSA more than tPSA in serum. In PCa hK2 more closely correlates with total cancer volume and high grade PCa volume compared with tPSA or fPSA.